Clinical Profile of Fibrocalculous Pancreatic Diabetes Cases: A Diabetes Entity Unique to Tropics - Chatterjee, Rupak; Halder, Prantiki; Samajdar, Shambo Samrat; Mukherjee, Shatavisa; Saha, Bibhuti (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Fibrocalculous pancreatic diabetes (FCPD) is a unique form of diabetes reported from tropical countries. Though classically described in young, lean and malnourished people from tropical countries with a low socioeconomic background, recent evidences suggest that this classical presentation of FCPD is changing. Objective: The present study aims to explore detail clinical presentations of encountered FCPD cases in a tertiary hospital in Eastern India. Methods: A prospective observational study included cases fulfilling the diagnostic criteria of FCPD. Each included patient was interviewed for their basic demographic profile, body mass index, family history and duration of diabetes mellitus. Clinical, biochemical and radiological investigations were done. Results:A total of 11 patients were studied. Mean age observed was 26.18 years, with majority having their disease diagnosed before the age of 30years. The classical triad of pain abdomen, steatorrhea and DM was present in only 3 cases.On clinical examination, only 1 patient was found to be hypertensive HbA1c>=8 percent. Neuropathy was the most common complication detected, followed by nephropathy and retinopathy. Straight X-ray Abdomen after proper bowel preparation showed presence of diffuse calcification involving the head, body and tail region in all the 11 cases, thus confirming the diagnosis. All the cases were managed medically with injectable insulin. Conclusion: Although insights have been gained into its natural history, the etiopathogenesis continues to be elusive. Despite the low prevalence of the disease, clinicians practicing in tropical countries should always keep in mind FCPD as a differential diagnosis during evaluation of a young diabetic patient, especially if patient is lean and there is a history of abdominal pain or steatorrhea with absence of ketosis. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 249-253